2020
DOI: 10.3389/fmicb.2020.00303
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of AISI 1045 Steel in Seawater in the Presence of Flavobacterium sp.

Abstract: A systematic comparison study was carried out to investigate the effect of Flavobacterium sp. on AISI 1045 steel corrosion by weight loss, fluorescence microscopy (FM), surface analysis, cell count, pH measure, electrochemical impedance spectroscopy (EIS), and polarization curves. The impedances were considerably increased by Flavobacterium sp. between 1 and 7 day exposure and after 30 day exposure but considerably decreased by Flavobacterium sp. after 15 and 21 day exposure, which were supported by the I corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…5b, Table S2) after 24 h immersion in ethanol-based solution result from the formation of protective corrosion product layer and the consumption of oxygen in the immersion system. 9,73 We derive equations to calculate corrosion rate (CR) directly from PGSK quenching, and the rate is comparable with Tafel results. Figure 5c compares the CRs at different time points yielded from two methods: Tafel extrapolation (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…5b, Table S2) after 24 h immersion in ethanol-based solution result from the formation of protective corrosion product layer and the consumption of oxygen in the immersion system. 9,73 We derive equations to calculate corrosion rate (CR) directly from PGSK quenching, and the rate is comparable with Tafel results. Figure 5c compares the CRs at different time points yielded from two methods: Tafel extrapolation (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…However, corrosion issues can result in structural failure in both aqueous and in organic or mixed-solvents environments, which leads to enormous economic losses, injuries, and even death. [8][9][10][11][12][13][14][15][16][17][18][19][20] Particularly, oil and gas pipelines or fuel tanks come into contact with organic solvents regularly and their corrosion behavior is less predictable than metals in aqueous media. 21,22 To avoid such failures, it is essential to sense and quantify corrosion in different environments.…”
mentioning
confidence: 99%
“…MIC refers to the material degradation caused by microbial activities or corrosive microbial metabolites, which accounts for 20% of global corrosion costs [7][8][9]. Numerous studies have shown that some microorganisms can accelerate the corrosion of metals [10][11][12][13][14][15][16][17]. However, the effect of microorganisms on the corrosion resistance of organic coatings is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, corrosion issues can result in structural failure in both aqueous and in organic or mixed-solvents environments, which leads to enormous economic losses, injuries and even death. [8][9][10][11][12][13][14][15][16][17][18][19][20] To avoid such failures, it is essential to sense and quantify corrosion in different environments.…”
Section: Introductionmentioning
confidence: 99%